Analisis Penerapan Pasal 1365 KUHPerdata dalam Tindakan Pemerintah Daerah Lombok Barat sebagai Perbuatan Melawan Hukum - Muhammad Rizky Pratama; Nur Aisyah Rahmdani (Gema Cendekia Institute, 2026)
The application of Article 1365 of the Civil Code (KUHPerdata) regarding unlawful acts is crucial in assessing actions taken by local governments. This study aims to analyze the application of Article 1365 of the Civil Code in the actions of the West Lombok local government that are considered unlawful acts. In this context, unlawful acts can be defined as actions that violate the rights of others or applicable legal norms, which may cause harm to other parties. This study employs a legal-normative method, utilizing an analytical approach to relevant legislation, as well as a case study of the actions taken by the West Lombok local government. The results of the study indicate that although the local government possesses the authority to formulate policies, certain actions taken have violated the legal principles established in Article 1365 of the Civil Code, such as non-compliance with applicable legal procedures or the presence of elements of negligence that cause harm to others. This study concludes that the application of Article 1365 of the Civil Code in cases of unlawful acts by the West Lombok local government needs to be reinforced with stricter oversight to ensure justice for the community.